Personal maturity and choice of strategies of behaviour in the conflict of service sector employees - V. A. Zhuravlev; S. B. Taisaeva (Вестник университета, 2025)
This article examines the relationship between personal maturity and conflict behaviour strategies among service sector employees. Personal maturity is a complex set of personal properties that includes a number of parameters such as self-actualisation, responsibility as well as emotional, spiritual and moral maturity. Conflict behaviour strategies are behavioural coping of human interaction in a conflict situation. Personal characteristics of the service sector employees include such key components as extraversion, neuroticism, high emotional intelligence and empathy. Using 5 methods that comprehensively diagnose human personal maturity as well as the priority of a conflict behaviour strategy and coping strategies in difficult situations, the authors reveal the relationship between the studied personality traits of the service sector employees. The research results have showed average and high levels of the personal maturity among the workers of this sector with the priority of such strategies as cooperation, adaptation and compromise. It is revealed that personally mature employees choose the following coping strategies: planning and positive reassessment. A negative relationship can be traced with such coping strategies as responsibility and compromise.